2014
DOI: 10.3389/fpls.2014.00331
|View full text |Cite
|
Sign up to set email alerts
|

Protein body formation in the endoplasmic reticulum as an evolution of storage protein sorting to vacuoles: insights from maize γ-zein

Abstract: The albumin and globulin seed storage proteins present in all plants accumulate in storage vacuoles. Prolamins, which are the major proteins in cereal seeds and are present only there, instead accumulate within the endoplasmic reticulum (ER) lumen as very large insoluble polymers termed protein bodies. Inter-chain disulfide bonds play a major role in polymerization and insolubility of many prolamins. The N-terminal domain of the maize prolamin 27 kD γ-zein is able to promote protein body formation when fused t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 56 publications
2
39
0
Order By: Relevance
“…For instance, maize Mucronate mutation forms a misfolded 16-kDa γ-zein that leads to irregular PB formation, but it could be rescued to restore normal PB by silencing the expression of the mutant 16-kDa γ-zein gene (34,35). Although 16-kDa γ-zein lost a large part of its N-terminal domain compared with 27-kDa γ-zein that was able to promote PB formation (36,37), a recent study showed that 16-kDa γ-zein acquired a new function in PB assembly (38). Furthermore, the 16-kDa γ-zein promoter lost all known conserved cis-elements present in other zein promoters (5) but acquired the cis-element ACGCAA, recognized by the corresponding NAC TFs, thereby restoring its endosperm-specific expression and synchronization with starch storage.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, maize Mucronate mutation forms a misfolded 16-kDa γ-zein that leads to irregular PB formation, but it could be rescued to restore normal PB by silencing the expression of the mutant 16-kDa γ-zein gene (34,35). Although 16-kDa γ-zein lost a large part of its N-terminal domain compared with 27-kDa γ-zein that was able to promote PB formation (36,37), a recent study showed that 16-kDa γ-zein acquired a new function in PB assembly (38). Furthermore, the 16-kDa γ-zein promoter lost all known conserved cis-elements present in other zein promoters (5) but acquired the cis-element ACGCAA, recognized by the corresponding NAC TFs, thereby restoring its endosperm-specific expression and synchronization with starch storage.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the 27-kDa γ-zein, its N-terminal region contains eight VHLPPP repeats and seven Cys residues that could form inter-chain disulfide bonds, which could be sufficient for ER retention (Llop-Tous et al , 2010). Recently it has been shown that progressive substitution of the seven Cys into Ser residues in the 27-kDa γ-zein could gradually increase its solubility and traffic to the vacuole via a wortmannin-sensitive pathway, leading to the proposal that the deposition of zeins in the ER evolves from storage protein sorting to vacuoles (Mainieri et al , 2014). Knock-down of the 27-kDa γ-zein resulted in severe reduction in PB number, but those remaining had normal size (Wu and Messing, 2010; Guo et al , 2013; Yuan et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, 27-kDa γ-zein RNAi lines exhibit a drastically reduced number of PBs, but with normal size (Wu and Messing, 2010; Guo et al , 2013). Further data indicates that 27-kDa γ-zein is retained at the ER through its N-terminal region that harbors eight Pro-rich repeats and seven Cys residues, possibly evolved from the storage-protein sorting to vacuoles pathway (Llop-Tous et al , 2010; Mainieri et al , 2014). In contrast, other γ-zeins (16- and 50-kDa) and 15-kDa β-zein RNAi lines have normal PB number but with reduced size, indicating that these γ- and β-zeins are necessary for PB filling but not initiation (Wu and Messing, 2010; Guo et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Williams), and lettuce (Lactuca sativa). In addition, two signal peptides, Zera ® (Mainieri et al 2014) andExtensin (De Loose et al 1991), were utilized to examine the potential roles of each on the accumulation of the recombinant IpaD protein in the plants under study. Meanwhile, an approach based on suppression of posttranscriptional gene silencing (PTGS) was employed using Cucumber mosaic virus (CMV) 2b protein (Goto et al 2007;Arzola et al 2011) to determine its effect on the production quantity of the current recombinant IpaD protein.…”
Section: Introductionmentioning
confidence: 99%